2011
DOI: 10.1017/s1751731110002673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrolyzed yeast supplementation in calf starter on immune responses to vaccine challenge in neonatal calves

Abstract: The effects of hydrolyzed yeast supplementation on growth performance, health and immune-physiological parameters in neonatal calves challenged with vaccine were investigated. Twelve Holstein calves were started in the experiment at 2 6 1 days of age and were studied for 35 days. Calves were randomly assigned to each of two dietary treatments, a control (CON) and hydrolyzed yeast (HY) group. The calves in the HY group received control calf starter supplemented with 0.2% HY. All calves were given calf starter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 31 publications
3
27
0
3
Order By: Relevance
“…Also Kim et al (2011) observed that calves from the hydrolysed yeast group showed better faecal and health scores after 3 weeks when compared with those in the control group. According to Chaucheyras-Durand et al (2008), yeast responses vary depending on the strain of yeast used, the nature of the diet and the physiological status of the animal.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Also Kim et al (2011) observed that calves from the hydrolysed yeast group showed better faecal and health scores after 3 weeks when compared with those in the control group. According to Chaucheyras-Durand et al (2008), yeast responses vary depending on the strain of yeast used, the nature of the diet and the physiological status of the animal.…”
Section: Discussionmentioning
confidence: 89%
“…However, results in dairy calves are inconsistent throughout the literature. Kim et al (2011) reported no difference in feed intake, liveweight or feed efficiency when neonatal calves received either control calf starter or starter supplemented with 0.2% of hydrolysed yeast. Moreover, Quigley et al (1992) observed a significant decrease in DM intake with supplemental yeast culture.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Altering the diet around the peripartum period and examining the effect of supplementation with safflower oil or palm oil have shown that the plasma concentrations of Hp and fibrinogen were greater in cows fed with a safflower oil than the palm oil, the conclusion being that the safflower oil supplement leads to an improved innate immune system better able to cope with infection in the postpartum period [211]. The effect of adding hydrolyzed yeast to the diet of calves on the response of Hp to live vaccine challenge (Hog cholera and Erysipelothrix insidiosa) was that the calves given the yeast supplement had a significantly higher Hp concentration on days 1 and 3 post vaccination than a control group [212] and could be better able to respond to infectious challenge.…”
Section: 3mentioning
confidence: 99%